THE CITY AS TEXT URBAN IDENTITY AND COMMUNALISM IN RAVAN AND EDDIE - Patel, Puspakantbhai Rameshbhai; Desai, Pankti Bharatbhai (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Kiran Nagarkar’s Ravan and Eddie (1994) remains a seminal text in Indian English literature for its satirical yet deeply socio-political portrayal of Mumbai’s chawl life, where space, identity, and communalism intersect in everyday practices. The novel positions the chawl as a microcosm of the city, where Hindu and Catholic communities coexist in an atmosphere of intimacy, surveillance, and latent hostility (Adarkar & Menon, 2004; Hansen, 2001). The text can be read as an urban palimpsest where the city itself becomes a legible script, echoing Roland Barthes’ (1972) notion of cultural semiotics and Michel de Certeau’s (1984) theorization of spatial practices. By employing humor and irony, Nagarkar narrates the resilience of marginalized subjects negotiating aspirations in a rapidly transforming metropolis, while also underscoring the precariousness of communal relations (Mehrotra, 2003; Chaudhuri, 2011). The narrative foregrounds how communalism in India is not confined to violent outbursts but is embedded within banal conversations, neighborhood gossip, and socio-religious stereotypes, aligning with Gyanendra Pandey’s (1990) conception of communalism as a historically constructed everyday phenomenon. This study employs textual analysis informed by postcolonial urban theory and cultural identity frameworks (Bhabha, 1994; Hall, 1990; Lefebvre, 1991) to argue that Ravan and Eddie encode Mumbai as both a lived city and a symbolic text, simultaneously cosmopolitan and fractured. Situating the novel alongside critical urban scholarship (Prakash, 2010; Patel, 2014; Chatterjee, 2020), the paper demonstrates how literature can illuminate the entanglement of urban identity and communal politics in post-independence India, making Nagarkar’s work a critical site for rethinking contemporary debates on multiculturalism, belonging, and the politics of urban citizenship.